Management of information technology projects - Schwalbe, Kathy (Singapore, 2011)
The future of many organizations depends on their ability to harness the power of information technology. and good project managers continue to be in high demand. Colleges have responded to this need by establishing courses in project management and making them part of the information technology, management, engineering, and other curriculum. Corporations are investing in continuing education to help develop effective project managers and project teams. This text provides a much-needed framework for teaching courses in project management, especially those that emphasize Management of Information Technology Projects.
Keywords: Information technology projects - Management; Project management